Role of IFNγ in pathogenesis of SARS-CoV-2 infection - A. A. Artamonov; Yu. V. Nikitin; M. E. Meshkova; A. M. Ivanov (Медицинская иммунология, 2022)
To date, there is no consensus explaining the relationship between varying concentrations of IFNγ and the severity of infection caused by SARS-CoV-2. The aim of this article was to analyze and formulate conclusions from the selected studies and publications, which, in sum, provide a potentially reasonable view on the role of IFNγ in COVID-19 pathogenesis. This article highlights current data on the immunological role of IFNγ which affects differentiation of naive T helper cells, acting as a polarizing factor. It activates the major histocompatibility complex (MHC) class I and II, by increasing the expression of MHC I/II subunits, inhibiting replication of the viral particles by initiating activation of interferon-stimulated genes followed by subsequent synthesis of antiviral proteins. Moreover, IFNγ activates the production of cytokines by T cells, enhancing cytotoxic activity of the T killers. IFNγ exerts immunostimulatory and immunomodulatory effects via STAT1, SOCS1 and PIAS genes, thus regulating activation of the JAK-STAT signaling pathway. A number of studies were considered where the patterns of changes in serum IFNγ concentration were examined in viral infections and SARS-CoV-2. We performed a systemic analysis of the results of studies that showed a relationship between high concentrations of IFNγ and COVID-19 severity. In a number of studies, the significantly high levels of IFNγ in COVID-19 patients were often associated with a poor outcome of the disease. The median values of the IFNγ concentration in severe COVID-19 were found to be significantly higher compared to the results obtained in the cases of moderate severity. It shows an increase, in parallel with viral load in the nasopharyngeal samples upon worsening of the clinical condition. Based on the data on the decreased IFNγ concentrations in convalescent patients, the mechanism of antagonism between IFNγ and IL-4 is considered, where the decreases serum concentrations of IFNγ along with increasing level of IL-4 may be an indirect proof of normal adaptive immune response with subsequent development of antibodies to SARS-CoV-2 and gradual elimination of the virus from the body. Moreover, the evidence is discussed that the patients harboring some parasitic infections (Toxoplasma gondii, Cryptosporidium, Blastocystis hominis, Giardia duodenalis, Entamoeba histolytica) with persistently elevated level of IFNγ are at reduced risk for severe course of COVID-19.